Daya Terima dan Kandungan Gizi Bolu Kukus berdasarkan Penambahan Sari Kulit Manggis (Garcinia Mangostana Linn) pada Adonan sebagai Pewarna Alami - Tesa, Tesa; Chandra, Filius; Putri, Satiti Kawuri (Prosiding Seminar Kesehatan Nasional, 2024)
hetic food colouring is usually used in steamed biscuits to create attractive colours that appeal to consumers. In an effort to diversify food products through the use of mangosteen rind juice, further processing is being undertaken, one of which is the use of mangosteen rind juice as a natural colouring agent on steamed biscuits. The purpose of this study was to determine the acceptability and nutritional content of steamed sponge cake with the addition of mangosteen rind juice as a natural colour. This research is an experimental study using a completely randomised design (CRD) with four treatments of adding (0ml, 10ml, 20ml, 30ml) mangosteen rind juice. Acceptability was tested using a hedonic method organoleptic test conducted by 30 untrained panelists. Nutritional content was tested, namely water content, ash content and vitamin C content. Acceptability test data were analysed using SPSS one-way ANOVA and Duncan's post hoc test. The acceptability of the steamed sponge cake with mangosteen juice added gets the best mean value preferred by the panelists, namely A4 (mangosteen juice added 20 ml) with a mean value of 4.01 (category likes). With a water content of 30.93%, an ash content of 1.11% and a vitamin C content of 14.05 mg/100g.  From the results of this study, it can be concluded that the addition of mangosteen peel juice to steamed sponge cake is significantly different in the aroma and flavour parameters, while the texture and colour parameters are not significantly different.